Comparison of multiple X-ray fluorescence techniques for elemental analysis of particulate matter collected on air filters. (August 2018) - Bilo, Fabjola; Borgese, Laura; Wambui, Anne; Assi, Ahmad; Zacco, Annalisa; Federici, Stefania; Eichert, Diane M.; Tsuji, Kouichi; Lucchini, Roberto G.; Placidi, Donatella; Bontempi, Elza; Depero, Laura E.
Abstract: This work reports on qualitative and semi-quantitative elemental analysis of particulate matter (PM) collected on PTFE membrane filters, for a source apportionment study conducted in Brescia (Italy). Sampling was undertaken in a residential area where an increase in Mn emissions has been highlighted by previous studies. Filters are measured by means of X-ray Fluorescence (XRF) based techniques such as micro-XRF and grazing incidence XRF using synchrotron radiation, Mo or W excitation sources, after applying an automatized sample preparation method. A heterogeneous distribution in PM shape, size and composition was observed, with features typical of anthropogenic sources. XRF measurements performed at various incidence angle, on large areas and different experimental setup were reproducible. The results demonstrate a successful comparison of the various XRF instrumentation, and the decrease in Mn content with the distance away from the identified emission source. This work highlights the potentialities of the presented approach to provide a full quantitative analysis, and ascertain its suitability for providing a direct, fast, simple and sensitive elemental analysis of filters in source apportionment studies and screening purposes. Highlights: PM10 is collected on PTFE filters for source apportionment in a polluted area. Elemental analysis is performed by different XRF based techniques. A new sample preparation method for membrane filters is used. Results show the potential of the proposed approach for screening purposes.